Development of job demands, decision authority and social support in industries with different gender composition – Sweden, 1991–2013 - Sara Cerdas; Annika Härenstam; Gun Johansson; Anna Nyberg (BMC Public Health, 2019)
Abstract Background This study aims to explore the development of job demands, decision authority and social support within and between industries with different gender composition in Sweden between 1991 and 2013. Methods Cross-sectional data from 12 waves of the Swedish Work Environment Surveys (1991 to 2013), comprising in total 109,698 respondents, were used. Industries were classified in 7 categories according to its gender composition and main activity, comprising two female-dominated, three gender-mixed and two male-dominated industries. Proportions of workers reporting high job demands, low decision authority and poor social support between 1991 and 2013 were calculated. Logistic regression analyses were performed to estimate variation across time, using 1991 as the reference category, and between industries, using knowledge intensive services as the reference category. Estimates for high job demands, low decision authority and poor social support were presented as average marginal effects (AMEs). Results The probabilities of reporting low decision authority were higher in education and health and social care during the whole study period, for both genders, compared with the reference category of knowledge intensive services. The probability of having high job demands were higher for men and women in education, and women in health and social care, compared with the reference category. Men in the male dominated industries had increased job demands over time, compared to the beginning of the study period (1991). The probability of reporting poor social support was higher in the later than in the earliest time period for women in the female-dominated industry health and social care as well as in the gender-mixed labour intensive services industry. Conclusions There has been a negative development of job demands and decision authority in the female-dominated industries education and health and social care in Sweden, whereas social support has developed more negatively for women in health and social care and in labour intensive services.